Heterogeneous cobalt-saponite catalyst for liquid phase air oxidation of p-cresol - Kshirsagar, Vikas S.; Garade, Ajit C.; Patil, Kashinath R.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2009)
Heterogeneous Co-saponite was found to be an efficient catalyst for the liquid phase oxidation of p-cresol under mild conditions. Divalent cobalt tons were found to be in both the tetrahedral and octahedral positions of the saponite clay. Studies on the effect of reaction parameters showed that the rate of reaction increased with increase in Co loading from 5 to 13% and then remained constant up to 30% of Co loading, while the rate of oxidation showed a first-order dependence on the partial pressure of oxygen up to 300 kPa. Results of oxidation experiments over Co-saponite, in an Inert atmosphere, and the XPS studies Suggest Mars-van Krevelen pathway operating, which involves lattice oxygen of Co-saponite in the liquid phase oxidation of p-cresol.

Hydroxyalkylation of p-Cresol to 2,2 `-methylenebis(4-methylphenol) using Sn/Si-MCM-41 catalysts - Garade, Ajit C.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Rode, Chandrashekhar V. (Chemistry Letters, 2010)
Sn/Si-MCM-41 has exhibited an excellent catalytic activity [70% product yield with 88% selectivity to 2,2'-methylenebis(4-methylphenol)] for the selective hydroxyalkylation of p-cresol. At equal level of Sn loading, Sn/Si-MCM-41 prepared by direct hydrothermal synthesis showed higher activity than Sn-impregnated Si-MCM-41 catalyst.